Molecular iodine synergized and sensitized neuroblastoma cells to the antineoplastic effect of ATRA. Issue 12 (December 2020) - Mendieta, Irasema; Rodríguez-Gómez, Gabriel; Rueda-Zarazúa, Bertha; Rodríguez-Castelán, Julia; Álvarez-León, Winniberg; Delgado-González, Evangelina; Anguiano, Brenda; Vázquez-Martínez, Olivia; Díaz-Muñoz, Mauricio; Aceves, Carmen
Abstract : Neuroblastoma (NB) is the most common solid childhood tumor, and all-trans retinoic acid (ATRA) is used as a treatment to decrease minimal residual disease. Molecular iodine (I2 ) induces differentiation and/or apoptosis in several neoplastic cells through activation of PPARγ nuclear receptors. Here, we analyzed whether the coadministration of I2 and ATRA increases the efficacy of NB treatment. ATRA-sensitive (SH-SY5Y), partially-sensitive (SK-N-BE(2)), and non-sensitive (SK-N-AS) NB cells were used to analyze the effect of I2 and ATRA in vitro and in xenografts (Foxn1 nu/nu mice), exploring actions on cellular viability, differentiation, and molecular responses. In the SH-SY5Y cells, 200 μM I2 caused a 100-fold (0.01 µM) reduction in the antiproliferative dose of ATRA and promoted neurite extension and neural marker expression (tyrosine hydroxylase (TH) and tyrosine kinase receptor alpha (Trk-A)). In SK-N-AS, the I2 supplement sensitized these cells to 0.1 μM ATRA, increasing the ATRA-receptor (RARα) and PPARγ expression, and decreasing the Survivin expression. The I2 supplement increased the mitochondrial membrane potential in SK-N-AS suggesting the participation of mitochondrial-mediated mechanisms involved in the sensibilization to ATRA. In vivo, oral I2 supplementation (0.025%) synergized the antitumor effect of ATRA (1.5 mg/kg BW) and prevented side effects (body weight loss and diarrhea episodes). The immunohistochemical analysis showed that I2 supplementation decreased the intratumoral vasculature (CD34). We suggest that the I2  + ATRA combination should be studied in preclinical and clinical trials to evaluate its potential adjuvant effect in addition to conventional treatments.